Proses Metakognitif Siswa Dalam Menyelesaikan Masalah High Order Thinking - Jojor Janni Astuti Sigalingging; Makbul Muksar; Abdul Qohar (Graduate School of Universitas Negeri Malang, 2019)
Abstract: Metacognitive plays an important role in supporting students' success in solving High Order Thinking questions. The ability to think high-level includes analyzing, evaluating, and creating. Based on the type metacognitive consists of awareness, regulation, and evaluation. The data collected in this study is descriptive because the main data from this study are verbal data in the form of student expressions. This study aims to describe the metacognitive process of students in solving high order mathematical thinking problems. The metacognitive process of the type of awareness occurs when students try to understand the High Order Thinking problem and rethink what was previously known from the problem. metacognitive process type of regulation occurs when students rethink work steps and strategies that will be used in solving High Order Thinking problems. The metacognitive process type of evaluation occurs when students feel doubtful about the answers obtained, so rethink the results and check the truth of the answers obtained.Abstrak: Metakognitif memainkan peran penting dalam mendukung kesuksesan siswa menyelesaikan soal High Order Thinking. Kemampuan berpikir tingkat tinggi, meliputi menganalisis, mengevaluasi, dan mencipta. Berdasarkan jenisnya metakognitif terdiri dari awareness, regulation, dan evaluation. Data yang dikumpulkan pada penelitian ini bersifat deskriptif karena data utama dari penelitian ini adalah data verbal yang berupa ungkapan-ungkapan siswa. Penelitian ini bertujuan untuk mendeskripsikan proses metakognitif siswa dalam menyelesaikan soal high order thinking matematika. Proses metakognitif jenis awareness terjadi saat siswa berusaha untuk memahami soal High Order Thinking dan memikirkan kembali apa yang diketahui sebelumnya dari soal. proses metakognitif jenis regulation terjadi saat siswa memikirkan kembali langkah kerja dan strategi yang akan digunakan dalam menyelesaikan soal High Order Thinking. Proses metakognitif jenis evaluation terjadi saat siswa merasa ragu dengan jawaban yang diperoleh sehingga memikirkan kembali hasil dan memeriksa kebenaran jawaban yang diperoleh.